Handling fragmented database replication through binary vote assignment grid quorum - Ainul Azila, Che Fauzi; Noraziah, Ahmad; Noriyani, Mohd Zain; Beg, A. H. (Science Publications, 2011)
Problem statement: Organizations critically needed to supply recent data to users who may be geographically remote, while at the same time handle a volume request of distributed data around multiple sites. The storage, availability and consistency are important issues to be addressed in order to allow distributed users efficiently and safely access data from many different sites. Approach: Data replication is a way to deal with this problem since it provides user with fast, local access to shared data and protects availability of applications because alternate data access options exist. Handling fragmented database replication becomes challenging issue to administrator since the distributed database was scattered into split replica partitions or fragments. Results: This study presented a new mechanism on how to handle the fragmented database replication through the Binary Vote Assignment on Grid Quorum (BVAGQ). We address how to build reliable system by using the proposed BVAGQ for distributed database fragmentation. Conclusion: The result shows that managing fragmented database replication and transaction through proposed BVAGQ is able to preserve the data consistency.